Team-based learning in online education: the development of students’ creative thinking skills in digital art - Le, Siyu (Education and information technologies, 2023)
A person cultivates their creative skills influenced by various types of activities. The purpose of the work is to study the peculiarities of the development of students’ creative thinking skills, which are interrelated with the development of appropriate stages of team teaching, as well as to determine the impact of creative thinking on the indicators of academic performance and motivation to learn. The authors used the methods of sociological survey, which allowed them to determine that the largest number of students had mastered the skills of discipline (27%) and emotionality (21%) to a greater extent at the initial stage of the study. The results showed that 11% of the students in creative subjects (painting, digital art) and 7% of students in general disciplines (history, sociology, pedagogy, mathematics, physics, Chinese, cultural studies) had their academic performance at a high level before the start of online learning. The process of online teaching to paint was based on teamwork using the technologies of online education through educational online platform in the context of digital art. The results of the survey showed that the students had developed their creative skills significantly after training. The development of creative manner (29%) and analytical thinking (28%) were most popular. The authors determined that 88% of the students had received high grades in creative disciplines and 83% of the students in general academic disciplines after training. Most students were characterized by a high level of knowledge. The results are valuable for researchers who study the relationship between the development of creative skills and knowledge in general academic subjects, as well as strive to develop new curricula.